Pengembangan E-LKPD dengan Pendekatan SETS (Science, Environment, Technology, and Society) untuk Meningkatkan Keterampilan Berpikir Kritis pada Materi Sistem Reproduksi - ndah Lailatul Adhiyah; Kartika Ratna Pertiwi (Postgraduate, University of Mataram, 2024)
This study aims to develop electronic Student Worksheet (known with E-LKPD) with the SETS (Science, Environment, Technology, and Society) approach model to improve the critical thinking skills of high school grade XI students on reproductive system material. The SETS approach is used to stimulate critical thinking skills in problem-solving-oriented situations. The development model of this research is the ADDIE (Analysis, Define, Design, Development, Disseminate, Evaluation) development model. The research design uses a pretest-posttest control group design. The subjects of the study were 70 students in class XI of SMA Negeri 1 Depok. The development of E-LKPD was carried out with the help of iSpring. Validation is measured based on expert validation and limited trial results. The results of this study show that E-LKPD is declared very feasible and the results of the response to the use of E-LKPD have perfect criteria. The results of the wide-scale test showed that in the experimental class that applied the SETS approach, there was an increase in critical thinking skills with an average posttest score of 84.8 with the results of the gain score test in moderate criteria. Meanwhile, the control class also experienced an increase in critical thinking with an average posttest score of 77.62 with the results of the gain score test in low criteria.